Current Subjects in Russian Historical Research: Reflection in the LBC - D. O. Rusin (Библиосфера, 2024)
The first issue of the modernized Medium Tables of the Library Bibliographic Classification (LBC) – the national classification system of the Russian Federation – was published in 2001. They were to systematize literature on the social and human sciences, including history. Their analysis was made. The revision and clarification of the conceptual apparatus were performed, the historical periodization was clarified, the ideological division was eliminated. In 2022 the first stage of the LBC Medium Tables modernization was over, but the Library Bibliographic Classification Research and Development Center in the Russian State Library again faces with the task their updating again, which is again to begin with the sociohumanitarian sections. The historical science has continued its development over the past years: the methodology has been improved, and new lines of investigation have emerged. All this needs to be reflected in the LBC schedules. The aim of this article is to analyze the scientific works on the history of Russia, published from 2018 to 2023 and make proposals for adjusting the LBC Medium Tables. The interdisciplinary nature of modern historical research is emphasized, the most popular historical disciplines are mentioned, which include new social history, regional history, the history of everyday life, gender history, etc. The author proposes to make some changes to the historical sciences section of the LBC Medium Tables. They are connected with new methodical instructions in subclasses on the theoretical basis and methodology of historical science, the history of historical science in Russia since the 1990s, changes in formulations and methodical instructions of special subdivisions in section “History”. These changes will make it possible to reflect the current subjects of the Russian historical research in the second edition of the medium LBC Tables.